MODEL PEMBELAJARAN TREFFINGER MENGGUNAKAN PENDEKATAN KONTEKSTUAL TERHADAP PROSES BELAJAR MATEMATIKA SISWA KELAS X SMK PERSADA - Fitriana Rahmawati; Nurashri Partasiwi (Epsilon: Jurnal Pendidikan Matematika, 2020)
Abstract: The problem in this study is "Is there any effect of the Treffinger Learning Model using a contextual approach on the mathematics learning outcomes of class X students in the even semester of SMK Persada Bandar Lampung in the 2018/2019 school year?". The purpose of this study was to determine the effect of the Treffinger Learning Model using a contextual approach on the mathematics learning outcomes of even semester X students of SMK Persada Bandar Lampung in the 2018/2019 school year. In this study the authors used the experimental method. The experimental method is a method that deliberately evokes an event or situation, then how the result. In other words, the experimental method is a method of experimental activity, so that students experience and prove what they have learned for themselves. Based on the data analysis that has been carried out using the formula, it is obtained to test the similarity of two averages by looking at the test criteria for the level of use obtained where the test criteria and are supported by complementary techniques, namely observation techniques on student learning activities, then "There is an Effect of Treffinger's Learning using the Treffinger approach contextual learning outcomes for students of class X SMK Persada Bandar Lampung in the 2018/2019 academic year" Keywords: Treffinger's Learning, contextual approach, mathematics learning outcomes